Documentation of Low-Resource Languages in Southern China in the Digital Era：Interdisciplinary Fieldwork, Practice, and Values - He, Yancheng; Zhiwei Xu (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
In the digital era, documenting low-resource languages in Southern China, especially minority and endangered languages in Southwest China, is of great significance. These languages, embodying distinctive cultural heritages and cognitive systems, are under threat from language shift and modernization. Rooted in documentary linguistics—a newly born and still growing field dedicated to comprehensively documenting languages through digital media technologies for dynamic recording, long-term preservation, and easy accessible dissemination—for about two decades, we have conducted a couple of projects in documenting several languages or dialects of the Tai-Kadai family, utilizing interdisciplinary fieldwork to preserve linguistic data and cultural heritages embedded in these languages, thus obtaining some achievements in language preservation and revitalization, enriching global linguistic diversity and cultural heritage. This comprehensive interdisciplinary approach, aligned with documentary linguistics’ methodologies of participatory recording and cross-disciplinary data integration, not only comprehensively documents language data but also integrates diverse cultural knowledge, bridging the gap between linguistics and other disciplines. It provides a new model for low-resource language documentation, highlighting the value of preserving linguistic and cultural diversity, and offers essential data for language preservation and research, cultural inheritance, and community development.